In Silico Study of Bioactive Compounds of Putat Leaf Extract (Planchonia valida) as Anti-Cancer Against the VEGFR2 Receptor - Bela, Anisa; Dewi, Tribuana Tungga; Prabawa, Satria; Khatib, Alfi; Latief, Madyawati; Tarigan, Indra Lasmana; Farid, Faizar; Nelson; Yusnaidar, Yusnaidar (Pendidikan Kimia FKIP Universitas Jambi, 2024)
Cancer is the process of forming new tissue that is abnormal and malignant. Efforts to discover anti-cancer drug compounds continue to be made to minimize the toxic effects of chemotherapy, so it is necessary to look for other alternatives to treat cancer. This research aims to determine the anti-cancer activity of putat plant bioactive compounds through identification of receptor targets and interaction studies using the molecular docking method against the VEGFR2 (Vascular endothelial growth factor receptor-2) receptor. The results showed that in the test of eight putat plant bioactive compounds the best results were obtained for the compound 3-oxo-N-(1,3-thiazol-2-yl) butanamide with a binding free energy value of -9.86 kcal-mol-1 with an inhibition constant value of 1.47 Micromolar. The best docking result has an inhibition constant value that is higher than the native ligand and has a binding free energy that is almost close to the binding free energy of the native ligand with an inhibition constant value of 42.38 Micromolar and a binding free energy value of 10.06 kcal-mol-1. Therefore, the results of the docking of the bioactive compound 3-oxo-N-(1,3-thiazol-2-yl) butanamide with the VEGFR-2 receptor are considered capable of being an alternative as a candidate for anti-cancer drugs.